2021
DOI: 10.1002/onco.13694
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of Cyclin Pathway Genomic Alterations Across 5,356 Prostate Cancers: Implications for Targeted Therapeutics

Abstract: The cyclin pathway may confer resistance to standard treatments but also offer novel therapeutic opportunities in prostate cancer. Herein, we analyzed prostate cancer samples (majority metastatic) using comprehensive genomic profiling performed by next‐generation sequencing (315 genes, >500× coverage) for alterations in activating and sensitizing cyclin genes (CDK4 amplification, CDK6 amplification, CCND1, CCND2, CCND3, CDKN2B [loss], CDKN2A [loss], SMARCB1), androgen receptor (AR) gene, and coalterations in g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The main characteristics of the eligible studies are shown in Table 1. Overall, 14 studies with 449 patients were included in the meta‐analysis 3,8–10,16–25 . The median number of patients enrolled in each study was 17 (range: 5–218), and the median age ranged from 65 to 77 years.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of the eligible studies are shown in Table 1. Overall, 14 studies with 449 patients were included in the meta‐analysis 3,8–10,16–25 . The median number of patients enrolled in each study was 17 (range: 5–218), and the median age ranged from 65 to 77 years.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, 14 studies with 449 patients were included in the meta-analysis. 3,[8][9][10][16][17][18][19][20][21][22][23][24][25] The median number of patients enrolled in each study Quality assessments were performed on the included studies (details summarized in Table S1). Seven studies were considered good quality, five studies were of moderate quality, and two studies were of poor quality.…”
Section: Study Characteristics and Quality Assessmentmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to illustrate a possible correlation between elevated serum CEA and certain ctDNA alterations in CRPC. Amplifications of AR, MYC, CDK6, RAF1, PIK3CA, BRAF , and MET have been observed in patients with prostate cancer, and amplification of KRAS has been documented to drive malignant potential in prostate cells in vitro 9,18–25 . CNAs in KIT and CCNE1 have not been reported in prostate cancer, but they have been associated with poor prognosis and aggressive behavior in other malignancies 26,27 .…”
Section: Discussionmentioning
confidence: 99%
“…Amplifications of AR, MYC, CDK6, RAF1, PIK3CA, BRAF, and MET have been observed in patients with prostate cancer, and amplification of KRAS has been documented to drive malignant potential in prostate cells in vitro. 9,[18][19][20][21][22][23][24][25] CNAs in KIT and CCNE1 have not been reported in prostate cancer, but they have been associated…”
Section: Copy Number Amplifications In Patients With Elevated Ceamentioning
confidence: 99%
“…Regarding Cyclin D1, its aberrant expression or amplification promotes the proliferation of malignant prostate cells, which makes it a prognostic marker and a promising therapeutic target [ 34 ]. In addition, preliminary studies suggest that the cyclin pathway in PCa plays an important role in the evolution of the disease to a castration-resistant stage, interacting with androgens [ 35 , 36 ]. Therefore, we suggest that complex 1 acts on hormone-responsive cells to prevent their progression to a more advanced stage of the disease, including the castration-resistant phenotype.…”
Section: Discussionmentioning
confidence: 99%